2015
DOI: 10.3122/jabfm.2015.04.150005
|View full text |Cite
|
Sign up to set email alerts
|

Regional Supply of Chiropractic Care and Visits to Primary Care Physicians for Back and Neck Pain

Abstract: Background Whether availability of chiropractic care affects use of primary care physician (PCP) services is unknown. Methods We performed a cross-sectional study of 17.7 million older adults who were enrolled in Medicare from 2010 to 2011. We examined the relationship between regional supply of chiropractic care and PCP services using Spearman correlation. Generalized linear models were used to examine the association between regional supply of chiropractic care and number of annual visits to PCPs for back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…13 Davis et al 14 showed an inverse relation between supply of chiropractors and visits to PCPs because of back and neck pain among 17.7 million Medicare enrollees. They estimated that chiropractic care is associated with 0.37 million fewer visits to PCPs annually at a cost savings of $83.5 million.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Davis et al 14 showed an inverse relation between supply of chiropractors and visits to PCPs because of back and neck pain among 17.7 million Medicare enrollees. They estimated that chiropractic care is associated with 0.37 million fewer visits to PCPs annually at a cost savings of $83.5 million.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…14 Numerous studies have assessed pain and functional impairment with the BPI across diverse populations (urban vs rural; different nationalities), and medical conditions (cancer, musculoskeletal pain), 6,[14][15][16] although fewer studies have focused on the use of the BPI among those seeking or referred for CAM services. [17][18][19][20] Comparing results from these studies with those from the present study requires caution about the generalizability to subsets of the population of members with different types of pain seeking CAM services in an IHDS.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…First, it may both help stem the growth of opioid use and also reduce healthcare expenditures for the treatment of spine pain. 12 Second, by offsetting demand for primary care services, 8 it may effectively expand the primary care workforce. Third, it may reduce demands on the SSDI program in two ways: initial use of CMT for back pain has been associated with reduced disability rates at one year after injury, 13 and avoidance of use of opioids has been associated with lower disability rates one year following injury.…”
Section: Clinical Suggestionsmentioning
confidence: 99%
“…A higher supply of DCs appears to offset patients’ demand for primary care physician services for their back and neck pain, 8 raising the possibility that a higher supply of DCs might also reduce the number of opioid prescriptions that physicians write. Therefore the purpose of this study was to determine whether a higher supply of DCs or the use of chiropractic manipulative therapy (CMT) might be associated with lower use of prescription opioids, as measured by either obtaining an opioid prescription or the daily dose of opioids among patients who obtained an opioid prescription.…”
Section: Introductionmentioning
confidence: 99%
“…12 Would increasing their understanding increase the effort to improve personal body mass index values? In another report, Davis et al 13 indicate that chiropractors seem to displace some visits for back and neck pain that would otherwise be seen by primary care physicians.…”
mentioning
confidence: 99%